Genome-Wide Identification of Histone Modifiers and Their Expression Patterns during Fruit Abscission in Litchi - Peng, Manjun; Ying, Peiyuan; Liu, Xuncheng; Li, Caiqin; Xia, Rui; Li, Jianguo; Zhao, Minglei (Frontiers in Plant Science, 2017)
Modifications to histones, including acetylation and methylation processes, play crucial roles in the regulation of gene expression in plant development as well as in stress responses. However, limited information on the enzymes catalyzing histone acetylation and methylation in non-model plants is currently available. In this study, several histone modifier (HM) types, including six histone acetyltransferases (HATs), 11 histone deacetylases (HDACs), 48 histone methyltransferases (HMTs), and 22 histone demethylases (HDMs), are identified in litchi (Litchi chinensis Sonn. cv. Feizixiao) based on similarities in their sequences to homologs in Arabidopsis (A. thaliana), tomato (Solanum lycopersicum), and rice (Oryza sativa). Phylogenetic analyses reveal that HM enzymes can be grouped into four HAT, two HDAC, two HMT, and two HDM subfamilies, respectively, while further expression profile analyses demonstrate that 17 HMs were significantly altered during fruit abscission in two field treatments. Analyses reveal that these genes exhibit four distinct patterns of expression in response to fruit abscission, while an in vitro assay was used to confirm the HDAC activity of LcHDA2, LcHDA6, and LcSRT2. Our findings are the first in-depth analysis of HMs in the litchi genome, and imply that some are likely to play important roles in fruit abscission in this commercially important plant.